A Case-matched Comparative Study of Laparoscopic Versus Open Distal Pancreatectomy. Issue 4 (August 2015) - Khaled, Yazan S.; Malde, Deep J.; Packer, Jessica; De Liguori Carino, Nicola; Deshpande, Rahul; O'Reilly, Derek A.; Sherlock, David J.; Ammori, Basil J.
<x xml:space="preserve">Abstract</x> Introduction: Although the laparoscopic approach to distal pancreatectomy for benign and malignant diseases is largely replacing open surgery in some centers, well-designed studies comparing these approaches are limited. We present a case-matched study that compares the outcomes of laparoscopic distal pancreatectomy (LDP) to open distal pancreatectomy (ODP). Methods: Of 112 patients (51 female) who underwent surgery between January 2002 and December 2011, 44 patients were matched on a 1:1 basis (22 LDP, 22 ODP) according to age, sex, and tumor size. Outcomes were compared on an intention-to-treat basis. Data shown represent median where appropriate. Results: The laparoscopic and open groups were comparable for age (57 vs. 59.9 y, P=0.980), sex distribution (P=1.000), tumor size (3 vs. 4 cm, P=0.904), and the frequency of benign versus malignant disease (P=0.920). LDP was associated with significantly lower blood loss (100 vs. 500 mL, P=0.001), higher spleen preservation rate (45% vs. 18%, P=0.029), as well as shorter high dependency unit stay (1 vs. 5 d, P=0.001) and postoperative hospital stay (5 vs. 14 d, P=0.017). There was no significant difference in operating time (245 vs. 240 min, P=0.602) and postoperative morbidity (13.6% vs. 27.2%, P=0.431). In patients with malignant disease, there were no differences in R0 resection margin status (90% vs. 85.7%, P=0.88), the numbers of lymph nodes retrieved (12.7 vs. 14.1, P=0.82), the 1- and 2-year survival rates (89% vs. 81%, P=0.54 and 74.2% vs. 71.5%, P=0.63, respectively), and the mean duration of survival (45 vs. 31 mo, P=0.157). Conclusions: The laparoscopic approach to distal pancreatectomy offers advantages over open surgery in terms of reductions in operative trauma and duration of postoperative recovery without compromising the oncologic resection.